Nitrogen Detection in Bulk Samples Using a D-D Reaction-Based Portable Neutron Generator. (29th January 2013) - Naqvi, A. A.; Al-Matouq, Faris A.; Khiari, F. Z.; Gondal, M. A.; Isab, A. A.; Khateeb-ur-Rehman; Raashid, M. A.; Dastageer, M.
Abstract : Nitrogen concentration was measured via 2.52 MeV nitrogen gamma ray from melamine, caffeine, urea, and disperse orange bulk samples using a newly designed D-D portable neutron generator-based prompt gamma ray setup. Inspite of low flux of thermal neutrons produced by D-D reaction-based portable neutron generator and interference of 2.52 MeV gamma rays from nitrogen in bulk samples with 2.50 MeV gamma ray from bismuth in BGO detector material, an excellent agreement between the experimental and calculated yields of nitrogen gamma rays indicates satisfactory performance of the setup for detection of nitrogen in bulk samples.